2017
DOI: 10.12913/22998624/68458
|View full text |Cite
|
Sign up to set email alerts
|

CNG Injector Research for Dual Fuel Engine

Abstract: The article presents the tests results of the prototype design of hydraulically assisted injector that is designed for gas supply into diesel engines. The construction of the injector allows for its positioning in the glow plug socket, so that the gas is injected directly into the combustion chamber. The cycle analysis of the four-cylinder Andoria ADCR engine with a capacity of 2.6 dm 3 for different crankshaft rotational speeds allowed to determine the necessary time for fuel injection. Because of that, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It should be pointed out that the mentioned problem of excessive hydrocarbon emissions due to valve overlap can be limited by gas injection directly to the combustion chamber. An example of such concept was presented by Majczak et al [14].…”
Section: Methodsmentioning
confidence: 99%
“…It should be pointed out that the mentioned problem of excessive hydrocarbon emissions due to valve overlap can be limited by gas injection directly to the combustion chamber. An example of such concept was presented by Majczak et al [14].…”
Section: Methodsmentioning
confidence: 99%
“…There are certain techniques to reduce NO X and PM emissions, but their simultaneous reduction is not an easy task. This is currently being done by fine-tuning the combustion parameters and the use of exhaust gas recirculation (EGR) (Majczak et al, 2017). Besides, it is also reported that around 30% of the carbon monoxide (CO) and hydrocarbon (HC) emissions are emitted by transport vehicles (Garg and Ravikrishna, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The gas fuels, which are used for this purpose, are mainly, compressed natural gas (CNG) and liquefied petroleum gas (LPG). These engines are currently used in Europe for urban passenger transport, goods, and garbage collection, constituting a market share of 50% (Majczak et al, 2017). However, this requires significant modification in the engine, thereby a complete change in the ignition method and hence costly.…”
Section: Introductionmentioning
confidence: 99%
“…Its widespread use is generally attributed to an uncomplicated installation of an additional alternative fuel supply system in almost every car originally fuelled with petrol. Current research works aim to explore the possibility of powering compression-ignition engines with this fuel [6,7,8,9,10]. However, along with the development of LPG fuelling methods, the same emphasis is placed on the dissemination of CNG fuelling of combustion engines.…”
Section: Introductionmentioning
confidence: 99%